Tradisi Menumbuk Padi dengan Jeungki sebagai Warisan Budaya Aceh - Khairunnisa (Sociale : Journal of Social Science, 2026)
This study discusses the tradition of pounding rice using Jeungki as one of the cultural heritages of Acehnese society that possesses historical, social, and cultural values. Jeungki is a traditional rice-pounding tool that has been used from generation to generation by rural communities in Aceh before the development of modern technology in agricultural processing. This tradition functions not only as an economic activity and a means of fulfilling food needs, but also as a medium of social interaction, mutual cooperation, and a symbol of togetherness within the community. This research aims to describe the use of Jeungki, the cultural values embedded within the tradition, and the challenges of its preservation in the era of modernization. The study employs a qualitative approach using observation, interviews, and documentation techniques involving communities that still maintain the use of Jeungki. The findings reveal that Jeungki embodies the values of cooperation, social solidarity, respect for ancestral traditions, and reflects the local wisdom of Acehnese society in utilizing environmentally friendly traditional technology. However, the existence of Jeungki has gradually declined due to changes in lifestyles and the increasing use of modern machinery. Therefore, preservation efforts are needed through cultural education, documentation of traditions, and introduction to younger generations so that Jeungki remains recognized as part of Acehnese cultural identity.